A Best Practice Database for Energy Management Initiatives in the Mining Industry - M. Y. Levesque (Canadian Institute of Mining, Metallurgy and Petroleum, 2013)
The Australian Government?s Energy Efficiency Opportunities (EEO) program launched in 2006 obliges companies that use more than 0.5 PJ (petajoule) or roughly 139 GWh (gigawatt hour) per year to conduct an energy assessment in order to identify measures to improve energy efficiency. The opportunities identified by the mining sector were assembled in the Mining Significant Opportunities Register that permitted companies not yet embracing and adopting an energy management program to see what those who are, were doing and how much energy was saved, and helps disseminate best practice. The measures can be filtered by company, year, category or equipment type. The creation of a central repository of energy efficiency initiatives is valuable but this existing database could be improved; fields identifying the energy and carbon emission savings associated with a given initiative are a surprising omission. Consequently it does not permit the relative effectiveness of different measures for energy and carbon reductions to be readily assessed. A review of energy management efforts implemented in the mining industry, published in peer reviewed journals, corporate sustainability reports or industry publications during the last 40 years has revealed many examples of best practice. However, the lack of a standardized reporting framework in any of these sources has made it difficult to assess the effectiveness and compare the adopted energy management measures ? just as is the case with the Australian register. In an attempt to address these issues, an improved database structure has been created for energy management measures from the mining industry which identifies energy and financial savings arising from energy management initiatives, classifies applications to specific processes or equipment, and recognizes leaders in the mining industry with respect to energy management. The structure of the register includes the key data relevant to energy management in mining that is absent in the Australian version. The mining industry energy management database has been made available in the public domain where stakeholders can examine the best practice examples. Mining energy champions may also contribute to the register by providing case studies; a standardized entry template affords a quality assurance dimension that is absent in other reporting initiatives. Adoption of this database with its standardized reporting mechanism will enhance transparency of the mining industry in energy matters and help it maintain its social license to operate.